Dissolved inorganic nitrogen in a tropical estuary in Malaysia : transport and transformation - Aazani, Mujahid; Mohd Fakharuddin, Muhamad; Müller, Moritz; Shan, Jiang; Jie, Jin; Ying, Wu; Kun, Zhu; Guosen, Zhang; Sien, Edwin Aun Sia; Holt, Faddrine Ajon Jang (Copernicus Publications on behalf of the European Geosciences Union., 2019)
Dissolved inorganic nitrogen (DIN), including nitrate, nitrite and ammonium, frequently acts as the limitation for primary productivity. Our study focused on the transport and transformation of DIN in a tropical estuary, i.e., the Rajang River estuary, in Borneo, Malaysia. Three cruises were conducted in August 2016 and February–March and September 2017, covering both dry and wet seasons. Before entering the coastal delta, decomposition of the terrestrial organic matter and the subsequent soil leaching was assumed to be the main source of DIN in the river water. In the estuary, decomposition of dissolved organic nitrogen was an additional DIN source, which markedly increased DIN concentrations in August 2016 (dry season). In the wet season (February 2017), ammonium concentrations showed a relatively conservative distribution during the mixing, and the nitrate addition was weak. La Niña events induced high precipitations and discharge rates, decreased reaction intensities of ammonification and nitrification. Hence similar distribution patterns of DIN species in the estuary were found in September 2017 (end of the dry season). The magnitude of riverine DIN flux varied between 77.2 and 101.5 t N d−1 , which might be an important support for the coastal primary productivity.